Ilmu ikhlas : memburu bayangan Tuhan / HM. Nasruddin Anshori CH., H. Marsudi Dulfatah; editor, Hj. Ela S. Nurlaela Zahrah - NASRUDDIN ANSHORIY CH, HM; Marsudi Dulfatah , H.; Ela S. Nurlaela Zahrah , Hj. (Deepublish, 2015)
xii, 188 hlm. ; 20 cm.